Effectiveness of Online Learning: The Learning Methods and Media - Hesty Prima Rini; Dewi Khrisna Sawitri (Yayasan Ilomata, 2022)
Online distance learning has been implemented as the most possible alternative at this time for continuous learning while maintaining a distance to prevent the spread of the corona virus and obeying the rules not to gather in one place. Research was conducted to investigate the effectiveness of online learning by distributing questionnaire through the google form link. Data were obtained from 112 students related to media and learning methods that support the implementation of effective online learning . The result showed that 71% or 80 students mentioned that online learning at their university is effective. Blended Learning which is a combination of system synchronous learning and asynchronous learning is chosen by the majority of respondents. Related with the learning media, the use of google meet is the most popular learning media because apart from being able to be used as a medium in synchronous learning, it can also be used in the synchronous learning through Google classroom.